Understanding Revenue Administration : An Initial Data Analysis Using the Revenue Administration Fiscal Information Tool - Lemgruber, Andrea (Departmental Papers; Departmental Paper ;, 2015)
During the past few years, the Fiscal Affairs Department (FAD) has developed the Revenue Administration Fiscal Information Tool (RA-FIT), a tax and customs data gathering initiative. This paper, the first of its kind internationally given the number of countries covered, analyzes the results of the first round of RA-FIT data for 85 countries. It begins the process of making summarized cross-country information available to revenue administrations, in particular in developing economies, to help them improve their performance. Topics covered include performance measurement, institutional arrangements, and core operations of tax and customs administration. RA-FIT is in its second round of data gathering, now via an online portal; these data will be analyzed and in future made available to participating countries and technical assistance partners/donors through an online dissemination platform.